Tunable Nanopore Arrays as the Basis for Ionic Circuits - Lucas, Rachel A; Siwy, Zuzanna S (ACS applied materials & interfaces, 2020)
There has been considerable interest in preparing ionic circuits capable of manipulating ionic and molecular transport in a solution. This direction of research is inspired by biological systems where multiple pores with different functionalities embedded in a cell membrane transmit external signals and underlie all physiological processes. In this manuscript, we describe the modeling of ion transport through small arrays of nanopores consisting of 3, 6, and 9 nanopores and an integrated gate electrode placed on the membrane surface next to one pore opening. We show that by tuning the gate voltage and strategically placing nanopores with nonlinear current-voltage characteristics, the local signal at the gate affects ionic transport through all nanopores in the array. Conditions were identified when the same gate voltage induced opposite rectification properties of neighboring nanopores. We also demonstrate that an ionic diode embedded in a nanopore array can modulate transport properties of neighboring pores even without a gate voltage. The results are explained by the role of concentration polarization and overlapping depletion zones on one side of the membrane. The modeling presented here is intended to become an inspiration to future experiments to create nanopore arrays that can transduce signals in space and time.